(3efXheI aj eSGFd GdYOOs - (3eLghds ((3Ydj Hf eMeO QVG cGTa GdZWGAs)
(3ChdgG (B:s
(3HSe Gddg (B... (3abO HOG dj GdXfe HCMcGe GdpYnOO (B** (3hGdbUO EP fXeJ efgG eG jge SghdI GdMaX dg EPG fXe (B** (3hGdfKQ bO jYSQ MaXg Ydi bdjd MaX ef aMhd aVdG (B..s
(3BNQgG (B:s
.. (3hajg jQhi eGFI ehRYI Ydi JSGhj Mbg hLOYg (B** (3hHfJi GddHhf hGdeNGV hZjQgeG jLhR HGdJQGVj (B.s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3abg GdePGgH GdCNQis